Evaluation of the Effect of The Intra-Oral Factors on the Orthodontic Clear Aligners Color (Journal of Hama University, 2022)
The aim of the research is to evaluate the color changes that occur in orthodontic aligners after exposure to different oral environment factors in healthy adult patients (clinical study).orthodontic clear aligners were applied to a sample of (18) patients in two stages, they had mild crowding (2-3) mm and their ages ranged between (18-25) years. The color of the aligners was measured using a spectrophotometer (VITA Easyshade®, Germany) before and after exposure to the oral environment for 14 days.The exposure of the orthodontic aligners to the oral alignment led to a noticeable perceivable color change according to the National Bureau of Standards, where the color change mean values were 1.840 NBS for the first stage and 1.913 NBS for the second stage.The results of the current study demonstrated the lack of color stability of the orthodontic clear aligners during their application inside the mouth for a period of two weeks, and their pigmentation affected by the coloring agents consumed by patients, and consequently the low clinical aesthetic specifications of the orthodontic clear aligners.